(3GdJcejd hGdGJeGe dcJGH GdJYQja hGdEYdGes - (3eMeO Hf Ydj Hf GdNVQ GdZSGfi GdeYQha HGHf YSGcQs; (3YHO GdQMef Hf YHO Gddg GdNfYej GdSgjdj GdCfOdSj, CHh GdbGSe,J (B581 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eJee GdfYe hGdEMSGf CeG HYO aEf Chdi eG hLH UQa GdfXQ Edjg cJGH Gddg JYGdi s
(3BNQgG (B:s
(3hGbJUQJ Ydi PcQ GdCbhGd ai GdCcKQ ef ZjQ GSfGO LQjkG Ydi ePgH GdTjN ai cJGHg hGdMeO ddg QH GdYGdejf Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ HGdeOjfI GdefhQI(B((3JaSjQ (B59) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs